Going Global: Empowering Local Tourism of Bejijong’s Majapahit Heritage Village through English - Ascalonicawati, Adinda Prasty; Renta, Renta; Bontisesari, Bontisesari; Billah, Zakiyah Dania; Waro'i, Muhammad Rosyid Husnul (Eastasouth Journal of Effective Community Services, 2025)
In the era of national digital transformation, rural communities play a crucial role in sustaining local culture while adapting to technological change. This article reports a community service project aimed at empowering the residents of Bejijong Village, Mojokerto, East Java—home to the Majapahit Cultural Heritage Village—through training in social media utilization and English for tourism promotion. A workshop involving twenty local participants introduced strategies for using Instagram, Facebook, and TikTok as promotional tools, alongside English caption writing for global reach. Findings show that the workshop not only improved participants’ technical competence but also fostered mindset shifts regarding the role of digital platforms in economic and cultural development. The initiative demonstrates how digital literacy and multilingual content creation can enhance local identity visibility and economic sustainability in heritage-based tourism villages.